Implications of stipe and midrib morpho-anatomy on the taxonomy of Polypodiaceous ferns - Mondal, Sinjini; Moktan, Saurav (Phytotaxa, 2023)
After decades of uncertainty, the current fern classification corroborates traditional morphology with molecular evidence and is widely accepted. However, in the complex family Polypodiaceae, some major generic recircumscriptions are still open. The present study aims to provide a comprehensive account of the stipe and midrib morpho-anatomical features of polypodiaceous ferns from the eastern Himalayan region. Fresh specimens belonging to 24 species were collected from the study area. Macro-morphological features like colour, size, and texture were observed in the field with the aid of a dissection microscope while micro-morphological traits like scales, indument, and anatomical details were observed under a compound microscope. The type of tissues, arrangement of vascular bundles, the shape of xylem, and circumendodermal band seem to be of taxonomic significance. The UPGMA reveals comparable correlations with previously published clades and relationships based on morphological as well as molecular data.